"I Stand in the Middle of the Ocean" - Kaunda, Chammah J. (The ecumenical review, 2019)
The challenge of climate change for the South Pacific Island of Kiribati demands a 21st-century missional vision to help respond effectively to the hopes and fears of islanders. This article employs a "coconut theology" embedded within an Indigenous knowledge thought-system and the daily cultural experiences of the Kiribati people. Using coconut theology as a qualitative method, this study views climate songs as a source of primary data. The songs are collected and analyzed through a thematic approach. The findings demonstrate that songs play a critical role in the Kiribati people's culture, keeping their voice alive and helping them make sense of their experiences of climate change. Based on the findings, the article argues that climate change songs embody critical theologies that could help the church embrace Indigenous imagination in its search for contextual relevance and effective response to climate change.